Pengaruh Aktivitas Bermain Kelompok Terhadap Perkembangan Perilaku Sosial Pada Anak Prasekolah (Usia 4-6 Tahun) Penelitian Ouasy-Eksperimen 011 Tk Tunas Buana Surabaya - Dienar Hasri Djuwita, - (2006)
The main problem that mostly happened in preschool• children was the slowness in the development of the social behaviours. This disorders could happen because of some factors that influence it. One of the factor is less of stimulation playing activity given to the preschool children. The objective of this study was to analyze the effect of play group activities to the development of social behaviours in preschool children. This study used Quasy Experimental design. The population were the students of A class Tunas Buana Kindergarten Kelurahan Kalirungkut Kecamatan Rungkut Surabaya. The sample was recruited by using purposive sampling consisting of 22 respondents, taken according to the inclution criteria. They were divided into 2 group, treatment and control groups, each comprising 11 individuals. The independent variable in this research was play group activities and the dependent variables was the development of social behaviours. Data were collected by using observation sheet and count up the scor based on appropriate criteria of social behaviours which will be measured. They were analyzed by using Wilcoxon Signed Ranks Test and Mann Whitney U Test with level of significance p < 0,05. Results showed that play group activities affect the development of the social behaviours helping each other (p=0,015), the social behaviours interacts between friends (p=0,005) and also affect the social behaviours share what they have (p=0,005). It can be conclude that the gift of play group activities has significantly effect the development of the preschool chidren' s social behaviours. Important to do for futher research about play group activities to the development of motoricsensoric, cognitive and language in preschool chidren.